Hubungan Tingkat Pengetahuan Menyikat Gigi dengan Kebersihan Gigi dan Mulut Siswa Kelas IV dan V SDN 1 Kukuh Marga Tabanan 2025 - Ni Made Sirat; Asep Arifin Senjaya; Ni Nyoman Dewi Supariani; Ni Luh Komang Redita Aristya Dewi (Jurnal Kesehatan Gigi (Dental Health Journal), 2026)
According to data from the Indonesian Ministry of Health (2018), as many as 57.6% of the Indonesian population experienced dental and oral health problems during the last 12 months. Knowledge or cognitive is the most important domain for the formation of a person's actions. Brushing teeth properly is an important factor in maintaining dental and oral health. This study aims to determine the relationship between the level of knowledge of brushing teeth and dental and oral hygiene of students in grades IV and V of SDN 1 Kukuh Marga Tabanan 2025. This study is an observational study with a cross-sectional design. The types of data used are primary and secondary data using question sheets and direct examination. The results of the study on 33 respondents showed that the percentage of knowledge of brushing teeth was the highest, namely 58% in the sufficient category, with an average of 66.7. The percentage of students' dental and oral hygiene was the highest, 60.61% in the moderate category, with an average of 1.66. The highest percentage of dental and oral hygiene based on toothbrushing knowledge was found in students who had good knowledge of toothbrushing with moderate dental and oral hygiene of 66.67%. The results of the Spearman correlation analysis obtained a significance value of 0.466 greater than 0.05, there was no relationship between the level of knowledge and dental and oral hygiene of students at SDN 1 Kukuh Marga Tabanan. The conclusion in this study is that there is no relationship between the level of knowledge of toothbrushing and dental and oral hygiene.